2018
DOI: 10.4314/ejhs.v28i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Soil contamination rate, prevalence, intensity of infection of geohelminths and associated risk factors among residents in Bazou (west Cameroon)

Abstract: Background Soil-transmitted helminths (STH) infections remain an important public health problem in the tropics. This study aimed to evaluate the soil contamination rate and prevalence of infestations of geohelminth among residents in Bazou. Methods Four hundred (400) soil samples and 182 stool specimens were collected respectively from four sites and from inhabitants aged 1 to 40 years and above in 12 households. A questionnaire was administered to evaluate risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
1
12
0
2
Order By: Relevance
“…A study conducted by Tabi et al [42] also showed that open defecation is a risk factor for STH infections. Lack of hand washing was also reported as a risk factor for STH infection [43].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Tabi et al [42] also showed that open defecation is a risk factor for STH infections. Lack of hand washing was also reported as a risk factor for STH infection [43].…”
Section: Discussionmentioning
confidence: 99%
“…Different from other countries, for example, in Cameroon, Ascaris spp. eggs were most frequent (2%; 8/400) (Tchakounté et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This variation on the contamination profile may be related to the climatic influence as sand sediment may suffer greater influence, associated to wind and rain, than soil from public roads and squares (Silva et al, 2017). The influence of climatic conditions is important factors that affect the frequency of geohelminths in each region, justified by the fact that it favours the development and survival of eggs (Tchakounté et al, 2018). From an epidemiological point of view, these findings are relevant, especially considering the zoonotic aspect of those worms (Feldmeier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, clean sources of soil can be identified by community members and stored in designated locations within the household with ease of access. 44,45 Heat or elevated temperatures have been credited as methods with a potential to inactivate viruses within minutes. This is more so in enveloped virus such as SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%